The fabrication of micro-tapered optical fibres for sensing applications - Mullaney, Kevin (Cranfield University, 2016)
This thesis describes the processes used to manufacture optical fibre tapers and tapered long period gratings (TLPGs) using a CO2 laser. A semi-automated system for fabricating adiabatic and non-adiabatic tapers with repeatable physical dimensions has been developed. The tapers had waist diameters which were reproducible to within ± 0.5 μm. This system has also been used to fabricate TLPGs with periods ranging from 378 μm to 650 μm. Novel techniques to monitor the process of fabricating tapers were also explored. These techniques included; monitoring the transmission of the fibre using a spectrophotometer, using an in-line fibre Bragg grating (FBG) to measure the strain experienced by the optical fibre and the use of a near infra-red (NIR) camera to aid fibre alignment and laser power optimisation. The spectrophotometer allowed the optical properties of the tapers to be tailored for specific applications and the FBG provided strain data for process optimisation. The use of a NIR camera and an FBG as an in-line strain sensor are a novel use of these devices in a fibre tapering process. Tapers were also thin-film coated using sputtering techniques to form surface plasmon resonance sensors and their refractive index sensitivity was measured. A novel protein sensor based on gold nanoparticles deposited on a fibre taper is also reported, together with a lossy mode resonance taper sensor. The TLPGs which were fabricated, comprised of between 6 to 18 periods. The refractive index sensitivity of a 6 period TPLG was measured and was 372 nm/ RI. Their resonance bands had twice the bandwidth and exhibited a higher extinction, compared to UV-written long period gratings of a similar number of periods.